Eksistensi Sejarah, Nilai Pendidikan dan Makna Lawas Unru Karya Lalu Manca - Hary Murcahyanto; Bambang Eka Saputra; Mochamad Triyanto; Agus Riswanto; Lalu Mas’ud (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research is to describe the existence of history, educational value, and semiotic meaning of Lawas Unru by Lalu Manca. This study used descriptive qualitative method. Sampling using purposive sampling technique. The results of the study, namely the existence of history and educational values in Lawas Unru are: 1) The contents and message events in Lawas Unru contain resistance and contain messages to always hold on to honesty and trust, because in the end fate will show the truth. 2) The description of the contents of Lawas Unru explains the intended message so that the reader can empathize, 3) The choice of words contains educational values, namely wisdom, honesty, empathy, courage, and humility. The conclusion of the research is that the existence of Lawas Unru still maintains the use of words used in the imperial environment. while its educational value is to help readers gain knowledge and understand the world better, also being able to develop analysis and empathy in life. The real meaning in Lawas Unru is a picture of injustice, resulting in oppression which eventually gave birth to a resistance from the Sumbawa kingdom against the Dutch colonizers. Keywords: Educational Values, Existence, Lawas Unru, Meaning